Characteristics of the expression level of MMP-9 and TIMP-1 in hepatocellular and cholangiocellular liver carcinoma - V. A. Tumanskiy; M. D. Zubko (Patologìâ)
Aim. In order to determine the expression level of immunohistochemical markers of matrix metalloproteinase-9 (ММР-9) and its tissue inhibitor TIMP-1, and area of immunopositive cells а comprehensive histopathological, histological and immunohistochemical study of liver biopsy specimens was carried out in 94 patients, of which 55 (58.51%) patients had hepatocellular carcinoma and 39 (41.49%) – cholangiocellular carcinoma of liver.